cần gấp………………………………

Question

cần gấp………………………………
can-gap

in progress 0
Helga 1 year 2020-10-14T05:00:00+00:00 1 Answers 90 views 0

Answers ( )

    0
    2020-10-14T05:01:49+00:00

    5) $4x(x-2)+x=2$

    ⇔$4x(x-2)+(x-2)=0$

    ⇔$(4x+1)(x-2)=0$

    ⇔$4x+1=0$

        $x-2=0$

    ⇔$4x=-1$

        $x=2$

    ⇔$x=-1/4$

        $x=2$

    7)$x^4(x+2)=-x-2$

    ⇔$x^4(x+2)+(x+2)=0$

    ⇔$(x^4+1)(x+2)=0$

    ⇔$x^4+1=0$

        $x+2=0$

    ⇔$x^4=1$

        $x=-2$

    ⇔ $x=1$

        $x=-2$

     

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )